Psychiatric adverse events with hydroxychloroquine during COVID-19 pandemic - Emmanuel, Stip (Asian J Psychiatr, 2020)
• HCQ, well known in rheumatology, dermatology and tropical medicine is now considered in the treatment and prophylaxy for the SARS-CoVid19. • Mental and neurological manifestations should be assessed following the use of hydrochloroquine particularly following prophylactic use. • For acute malaria studies, HCQ was associated with high prevalenceof mental neurological manifestations amongst anti-malaria drugs. • Recommendations of using HCQ in COVID are variable and sometimes contradictory depending on agencies and countries.